Study on ammonia gas high temperature corrosion coupled erosion wear characteristics of circulating fluidized bed boiler. (February 2022) - Wu, Wenya; Wei, Bo; Li, Guanghui; Chen, Lijuan; Wang, Jianjiang; Ma, Jinrong
Highlights: The wear mechanism of 20G at different erosion conditions was analyzed. The coupling characteristics between erosion wear and ammonia gas high temperature corrosion was studied. The ammonia gas atmosphere promoted the erosion wear. Abstract: The phenomenon of erosion wear and high temperature corrosion will lead to thinning of tube wall, and serious tube burst will occur after long operation in circulating fluidized bed boiler. To obtain the effect on tubes by erosion wear and ammonia gas high temperature corrosion, a high-temperature gas–solid erosion wear test facility was used to simulate the SNCR conditions. This paper mainly studies the erosion wear characteristics, ammonia gas high temperature corrosion characteristics and coupling characteristics under different erosion speeds, erosion angles and heating temperatures. The results showed that the main erosion wear mechanism of 20G (SA106B of United States Standard) is cutting wear at low erosion angle, while deformation wear is the main action, and crack is the supplementary action at high erosion angle. The impingement velocity is varied from 29 to 43 m/s, the mass loss is varied from 0.0343 g to 0.1367 g. Erosion velocity plays an important role in affecting the wear of the specimen, while there is little effect of heating temperature on the wear of the material. In the studying of coupling characteristics, it is found that ammonia gas increases the critical temperature of the material. Furthermore, ammonia gas can accelerate the wear of specimens, but erosion wear is still the main cause of tube burst in fluidized bed boiler. In boiler operation, measures to prevent erosion wear should be taken to restrain coupling erosion.